Weighted Local Active Pixel Pattern (WLAPP) for Face Recognition in Parallel Computation Environment - Gundavarapu Mallikarjuna Rao (International Journal of Science and Engineering, 2013)
Abstract  - The availability of multi-core technology resulted totally new computational era. Researchers are keen to explore available potential in state of art-machines for breaking the bearer imposed by serial computation. Face Recognition is one of the challenging applications on so ever computational environment. The main difficulty of traditional Face Recognition algorithms is lack of the scalability. In this paper Weighted Local Active Pixel Pattern (WLAPP), a new scalable Face Recognition Algorithm suitable for parallel environment is proposed.  Local Active Pixel Pattern (LAPP) is found to be simple and computational inexpensive compare to Local Binary Patterns (LBP). WLAPP is developed based on concept of LAPP. The experimentation is performed on FG-Net Aging Database with deliberately introduced 20% distortion and the results are encouraging. Keywords — Active pixels, Face Recognition, Local Binary Pattern (LBP), Local Active Pixel Pattern (LAPP), Pattern computing, parallel workers, template, weight computation.